Utility of next-generation sequencing in identifying congenital erythrocytosis in patients with idiopathic erythrocytosis - Anžej Doma, Saša; Kraljić, Nika; Kristan, Aleša; Debeljak, Nataša; Maver, Aleš; Pajič, Tadej; Preložnik Zupan, Irena (Frontiers in Medicine, 2024)
Background Congenital erythrocytosis (CE) is increasingly recognized as the cause of erythrocytosis in patients in whom polycythemia vera and secondary acquired causes have been excluded. The aim of our study was to determine possible genetic background in patients with idiopathic erythrocytosis. Methods 40 patients with idiopathic erythrocytosis, referred to our institution in a 5-year period, were analyzed. We collected data on erythropoietin (Epo) levels, hemoglobin (Hgb), hematocrit (Hct), erythrocyte count, age, gender, past thrombotic events, concomitant diseases, and smoking status. CE was tested using next-generation sequencing (NGS), in the majority of patients also measurement of P50 and Hgb electrophoresis were performed. Patients with signs of iron overload were tested for genetic variants in the HFE gene. Results The median patient age at analysis was 46.5 years (range 22–73), with 37 out of 40 being males (93 %). The median Hgb, Hct and red blood cells count were 180 g/L, 0.51, 5.985 x 1012/L in men and 171 g/L, 0.50 and 5.68 x 1012/L in women, respectively. Epo levels were decreased in three, increased in one patient and within the normal range in the rest (median 7.55 mIU/mL; range 2.90–19.50). Eight patients (20 %) smoked. 32 (80 %) were treated with low-dose aspirin, and 20 (50 %) underwent at least one phlebotomy. Thromboembolic events were recorded in 2 patients (5 %). P50 was measured in 20 out of 40 patients, and it was above 24 mm Hg (3.12 kPa) in all of them. Hemoglobin electrophoresis was performed in 73 % of patients, with no abnormal Hgb detected. Variants in the HFE gene were found in 8 out of 40 patients (20 %), but in only one patient the results were associated with an increased risk for hemochromatosis. Although no pathogenic variants for CE were detected by NGS, two variants of uncertain significance, namely EGLN1 (NM_022051.2):c.1072C>T (p.(Pro358Ser)) and EGLN1 (NM_022051.2):c.1124A>G (p.(Glu375Gly)) were identified as strong etiologic candidates. Conclusion CE is an extremely rare condition. Genetic testing is advised in young individuals with a long-standing persistent erythrocytosis, possibly with a family history and after exclusion of more frequent secondary causes and polycytemia vera.